2016
DOI: 10.1002/ijc.29965
|View full text |Cite
|
Sign up to set email alerts
|

Cation-selective transporters are critical to the AMPK-mediated antiproliferative effects of metformin in human breast cancer cells

Abstract: The antidiabetic drug metformin exerts antineoplastic effects against breast cancer and other cancers. One mechanism by which metformin is believed to exert its anticancer effect involves activation of its intracellular target, adenosine monophosphate-activated protein kinase (AMPK), which is also implicated in the antidiabetic effect of metformin. It is proposed that in cancer cells, AMPK activation leads to inhibition of the mammalian target of rapamycin (mTOR) and the downstream pS6K that regulates cell pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
66
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(72 citation statements)
references
References 46 publications
(118 reference statements)
6
66
0
Order By: Relevance
“…It is possible that alternative transporters may also play a role in tumor cell metformin uptake contributing to direct metformin effects in vivo . A recent study found overexpressing OCT3 in BT-20 breast cancer cells (triple negative) positively correlated with metformin uptake, increasing metformin uptake >13-fold and decreasing proliferation 4-fold, which established a clear relationship between rate of selective metformin uptake and suppression of breast cancer cell proliferation (34). …”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…It is possible that alternative transporters may also play a role in tumor cell metformin uptake contributing to direct metformin effects in vivo . A recent study found overexpressing OCT3 in BT-20 breast cancer cells (triple negative) positively correlated with metformin uptake, increasing metformin uptake >13-fold and decreasing proliferation 4-fold, which established a clear relationship between rate of selective metformin uptake and suppression of breast cancer cell proliferation (34). …”
Section: Discussionmentioning
confidence: 94%
“…In concordance, hormonal regulation of kidney OCT2 expression was demonstrated in rats; testosterone upregulated OCT2 and estradiol moderately down-regulated OCT2 (35). Other studies identified variability in transporter expression profiles among luminal and basal (triple negative) breast cancer cell lines, with some triple negative lines showing higher levels of transporter expression, suggesting that heterogeneity in breast cancer tissue may also play a role in response to metformin (34). Triple negative breast cancer cells are more sensitive to metformin as compared to luminal lines (7).…”
Section: Discussionmentioning
confidence: 99%
“…32 Classic substrates include tetraethylammonium (TEA) and the parkinsonian neurotoxin 1-methyl-4-phenylpyridinium (MPP + ); clinically relevant drug substrates include famotidine, ranitidine, and metformin. 3335 …”
Section: Introductionmentioning
confidence: 99%
“…These include the organic cation transporters (OCT) 1–3, plasma monoamine transporter (PMAT) and the multidrug and toxin extrusion protein (MATE) 1 and 2 [1, 9]; OCT1 is critical for uptake into hepatocytes [10]. The expression of metformin transporters is variable across tumour cell lines and has been shown to be downregulated in breast tumour tissues in comparison to adjacent nonmalignant tissues [11]. In human cancer cell lines, which are known to express OCT1, metformin has been shown to decrease cell proliferation through inhibition of Complex I [12].…”
Section: Molecular Mechanismsmentioning
confidence: 99%